TANGGAPAN TAMU PADA KEBERSIHAN PUBLIC AREA (AREA UMUM) DEPARTEMEN HOUSEKEEPING DI HOTEL THE ZURI PEKANBARU - Dwi Masrifah; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Zuri Hotel Pekanbaru is one of the four-star hotels located in Pekanbaru City, Riau Province. The importance of maintaining the cleans of the hotel area to provide a positive image for the hotel and provide a goods image. The Housekeeping department must be keeping the entire hotel area clean, especially in the public area's because this area will give a great first impression to the guests. The method used in this study is mix method, The populations in this study were guests of The Zuri hotel Pekanba ru, and the research sample was 100 people. Then the data obtained were analyzed using the SPSS-25 application.This analysis includes: validity test, reliability test, simple linear regression test with normality assumption, linearity assumption, heteroscedasticity test, and determinant coefficient test. Based on the respondent's assessment distributed through questionnaires. It begins that the average guest answers were very expected (positive) on the cleanliness of the hotel public areas, with the level of respondent achievement of 1,571 with an average rating of 87.2 and that were classified as very good according to by TCR Sugiyono classification (2012: 207). Keywords : public area, hotel, cleanliness, response